Low-carbon warehousing practices and challenges: Insights from emerging country - Azian, Ibrahim; Fernando, Yudi; Tseng, Ming-Lang; Lim, Ming K. (Taylor and Francis Ltd., 2024)
This study aims to identify the issues, challenges, practices, and research agenda of low-carbon warehousing that the manufacturing industry faces in the low-carbon era. The debate on managing low-carbon and sustainable warehousing has gained popularity. Managing energy consumption and carbon emission in the warehouse has become a critical success factor towards low-carbon practices. Semi-structured, in-person interviews and phone conversations were used to gather the information for this study. The convenience sampling technique was used. The results showed that the internal challenges, such as financial constraint, perceived knowledge in low-carbon warehouses, and the top management support were the frequently highlighted domains. The findings revealed that organisational support, international standards certification, local authorities, and customer pressure were key success factors in implementing low-carbon warehouse practices. The companies have taken proactive measures to address the best practice of low-carbon warehouses.